2004
DOI: 10.1016/j.jtcvs.2003.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Bipulmonary transplants with lungs obtained from two non–heart-beating donors who died out of hospital

Abstract: bronchial tree or after endoscopic dilatation of a benign anastomotic stricture. Other causative factors have only been reported as solitary cases. 4 Among these, we have found in the literature just 1 other case in which the tracheogastric fistula presented in association with an auto-expandable esophageal wall-stent prosthesis. 5 Symptoms at presentation may range from mild to life-threatening. 3,4 Yet the possibility of a rapid deterioration of the patient's general condition should always be kept in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 5 publications
1
23
0
1
Order By: Relevance
“…Two assessment techniques have been reported for clinical DCD lung transplantation. One is the pulmonary artery flush technique using a solution based on the donor's blood [15][16][17], and the other is the ex vivo reperfusion technique [1,2]. The ex vivo evaluation technique is considered promising and is currently performed in several transplant institutions worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Two assessment techniques have been reported for clinical DCD lung transplantation. One is the pulmonary artery flush technique using a solution based on the donor's blood [15][16][17], and the other is the ex vivo reperfusion technique [1,2]. The ex vivo evaluation technique is considered promising and is currently performed in several transplant institutions worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NHBDs could be an excellent source of organs for transplantation. NHBDs are being increasingly accepted clinically as kidney, liver, lung, and pancreas donors, [14][15][16][17][18] while cardiac transplantation with NHBD allografts has not proceeded beyond the laboratory. In those NHBD experiments, the hearts were damaged by a combination of hypoxia and warm ischemia of at least 15-30 minutes in situ.…”
Section: Discussionmentioning
confidence: 99%
“…17 Here, two chest tubes are inserted and the lungs are cooled to 18°C inside the body with cold Perfadex solution for 2 h. The effi cacy of this technique has been investigated by several groups, 21,23,25,26,34 and topical in situ cooling has been used for clinical uncontrolled DCD (NHBD) cases. 17,[27][28][29] The preprocurement interval could be safely extended by topical in situ cooling up to 6 h postmortem allowing distant organ procurement or next of kin to spend more time with the deceased relatives.…”
Section: Lung Preservation For Clinical Dcds (Nhbds)mentioning
confidence: 99%
“…Administration of heparin after certifi ed death is possible with chest compressions to distribute the heparin around the circulatory system. 17,[27][28][29][30][31][32][33] In all the transplant centers in Table 1, except Cleveland, heparin was administered after death certifi cation. Investigators from the Okayama University have demonstrated the effi cacy of postmortem administration of heparin, 35 addition of a fi brinolytic agent (urokinase) 36 or recombinant tissue-type plasma to …”
Section: Timing Of Heparin Administrationmentioning
confidence: 99%
See 1 more Smart Citation